PENGARUH PENGETAHUAN DAN KEMUDAHAN TERHADAP KEPUTUSAN PENGGUNAAN SISTEM PEMBAYARAN SECARA ONLINE DI PEKANBARU - Mulyana, Sri; Sartika, Dewi (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
This study aims to analyze the influence of knowledge and ease of use on the purchasing decision using online payment systems in Pekanbaru. The development of digital technology has transformed the way consumers transact, with online payment systems becoming the primary choice for purchasing products or services. Consumer knowledge about online payment systems and the ease of use of these systems can influence their decision to adopt the system. This research employs a quantitative approach, collecting data through questionnaires distributed to respondents who actively use online payment systems in Pekanbaru. The collected data were analyzed using multiple linear regression to examine the influence of knowledge, ease of use, and purchasing decisions. The results indicate that consumer knowledge of online payment systems does not have a significant impact on purchasing decisions. In contrast, ease of use has a significant influence on purchasing decisions. This suggests that while consumers may have knowledge about online payment systems, the ease of use factor plays a more dominant role in influencing their decision to make a purchase. This study provides implications for online payment system developers to focus on simplifying the interface and improving user experience to enhance purchasing decisions. Keywords: Knowledge, Ease of Use, Purchasing Decision, Online Payment System